FAKTOR-FAKTOR PENDORONG PENYEBAB TERJADINYA KEMACETAN STUDI KASUS : KAWASAN SUKUN BANYUMANIK KOTA SEMARANG - Iwan Wijanarko; Mohammad Agung Ridlo (Jurnal Planologi, 2017)
Sukun region located in the southern city of Semarang is an activity node meetings between Semarang Upper and Lower part. In addition to the node activity, regional transport node Sukun is also because of the intersection between Setia Budi roads and highways. The rapid growth of traffic is felt at Setia Budi roads, this is because of the way as the initial point of entry into the city of Semarang from the south ( Yogyakarta - Solo ) both vehicles are going to Semarang and the entrance to the highway with a wide range of purposes. And trading activity and the presence of onsite services that are in the area resulted in increased activities of road users, the incidence of traffic generation and the high side barriers, which at certain hours of congestion and delays often occur. The research methodology used in this research is by using Deductive Quantitative Methods Rationalistic. With the technique of factor analysis and analysis of transportation, so it can be determined Level Of Service and factors - factors driving the cause of congestion in the area Sukun Banyumanik. The final results obtained from the analysis of the factors driving the causes of congestion on area Sukun is that congestion is due to the on site activity, the high capacity of the road, next to the barrier height and geometric conditions of the road.